On the cyclical behavior of fiscal policy in Egypt - Israa A. El Husseiny (Contemporary Economics, 2018)
Optimal fiscal policy is expected to behave in a countercyclical manner to stabilize economies during business cycles. In particular, the public expenditure-to-GDP ratio should go up during recessions and down during expansions, while the public revenues-to-GDP ratio should move in the opposite direction. As a result, the budget deficit-to-GDP ratio should rise during recessions and decline during expansions. While this behavior of fiscal policy is common in most developed countries, the situation is different in developing nations where, due to several financial and institutional factors, a procyclical policy is more common. Using a time series dataset for the Egyptian economy during the period (1981/1982-2013/2014), this study provides empirical evidence that Egypt has not been able to conduct a countercyclical fiscal policy. In addition, the analysis provided by this study indicates that while several financial and credit factors might contribute to this behavior of fiscal policy in Egypt, the institutional and political economy factors seem to have the dominant role in this regard.
Keywords: E32; E62; H60; 330; fiscal policy; cyclical properties; business cycles; output gap; Egypt state's general budget